The university's role in establishing social identity among university students - Rashid, Asst.Prof.Dr. Shirin Ibrahim Mohammed; Hussein, Asst.Prof.Dr. Shokhan Mahmoud; Suleiman, L. Tara Mahmoud (Sulaimani Journal for Humanities, 2025)
The aim of this study is Measuring the level of social identity among university students according to the social dimension, the cultural dimension, and the dimension of modernity and globalization. to determine the differences in statistical indicators of social identity among university students according to variable (gender, age, social background, specialty), as well as to identify the factors affecting the establishment of social identity among university students. This research consists of three parts, The first part consists of the general framework of the research and definition of the concept and presentation of previous research, The second part consists of discussing the tasks of the university and its role in consolidating social identity It is based on descriptive, social survey and comparative methods. The research community consists of students of University of Sulaimani. A sample of (377) students was randomly selected. The most important tools used in the research are the criteria (role of university in consolidating social identity among university students). Then, In the third part of the study, the results of the study are presented, which are: 1. The university has a positive role in consolidating social identity according to its dimensions (social, cultural, innovation and globalization). 2. There is no difference in statistical indicators for social identity measures regardless of the variables (gender, age, social background). 3. There are differences in statistical indicators for measuring social identity, with differences in specialty variables in favor of human specialties. 4. In the results of the factor analysis, the cultural factors were more obvious in the establishment and consolidation of social identity among the students University of Sulaimani. Finally, in the light of the results of the study, a number of recommendations and suggestions have been addressed to the relevant parties and researchers.
Keywords: Role; University; Social identity; University student